2021
DOI: 10.1186/s12934-020-01507-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, structural and biochemical characterization of a novel recombinant chlorophyllase from cyanobacterium Oscillatoria acuminata PCC 6304

Abstract: Background Chlorophyllase catalyzes the hydrolysis of chlorophyll and produces chlorophyllide and phytol. Cyanobacterial chlorophyllases are likely to be more highly heterologously expressed than plant chlorophyllases. A novel recombinant chlorophyllase from the cyanobacterium Oscillatoria acuminata PCC 6304 was successfully expressed in Escherichia coli BL21(DE3). Results The putative N-terminal 28-amino-acid signal peptide sequence of O. acumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated the importance of the catalytic triad (Ser-Asp-His) for CaCLH activity [ 29 ]. In one of the studies, one catalytic residue (Ser-Asp-His) was replaced with other residues, and the activity of CLH was either reduced or completely lost [ 10 , 29 , 30 ]. In this study, introduction of three mutations into the putative catalytic triad of SlCLH1 (S135, D162, and H239) showed the complete loss of CLH activity ( Figure 6 C).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have demonstrated the importance of the catalytic triad (Ser-Asp-His) for CaCLH activity [ 29 ]. In one of the studies, one catalytic residue (Ser-Asp-His) was replaced with other residues, and the activity of CLH was either reduced or completely lost [ 10 , 29 , 30 ]. In this study, introduction of three mutations into the putative catalytic triad of SlCLH1 (S135, D162, and H239) showed the complete loss of CLH activity ( Figure 6 C).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the N-terminal peptide processing of CLHs plays a contradictory role in their Chl dephytylation activity. For example, the chlorophyllases from Pachira macrocarpa and Cyanobacterium Oscillatoria cuminata PCC6304 were functionally inactive when the N-terminal peptide was removed [ 8 , 10 ]. However, CLH lacking the N-terminal 21 amino acids from Citrus sinensis showed more enzymatic activity in vivo [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that recombinant CyanoCLH preferred hydrolyzing bacteriochlorophyll a from R. sphaeroides. The characterization of a chlorophyllase (OaCLH) from the cyanobacterium Oscillatoria acuminata PCC 6304 was reported [130]. This study demonstrated that the substrates of recombinant OaCLH were chlorophyll a, chlorophyll b, bacteriochlorophyll a, and pheophytin a, and chlorophyll b and chlorophyll a were especially preferred.…”
Section: From Chlorophyll To Chlorophyllide a By Chlorophyllasementioning
confidence: 92%